MENGHITUNG DAMPAK TANGGUNG JAWAB SOSIAL PERUSAHAAN - Hakim, M. Lukman (Jurnal Legislasi Indonesia, 2009)
Corporate Social Responsibility (CSR) is a form of corporateself-regulation integrated into a business model. Ideally, CSRpolicy would function as a built-in, self-regulating mechanismwhereby business would monitor and ensure their adherenceto law, ethical standards, and international norms. Businesswould embrace responsibility for the impact of their activitieson the environment, consumers, employees, communities,stakeholders and all other members of the public sphere.Furthermore, business would proactively promote the publicinterest by encouraging community growth and development,and voluntarily eliminating practices that harm the publicsphere, regardless of legality. Essentially, CSR is the deliberateinclusion of public interest into corporate decision-making, andthe honoring of a triple bottom line: People, Planet, Profit. Thepractice of CSR is subject to much debate and criticism.Proponents argue that there is a strong business case for CSR,in that corporations benefit in multiple ways by operating witha perspective broader and longer than their own immediate,short-term profits. Critics argue that CSR distracts from thefundamental economic role of businesses; others argue that itis nothing more than superficial window-dressing; others arguethat it is an attempt to pre-empt the role of governments as awatchdog over powerful multinational corporations. This articlefocused on how CSR implemented in mining corporations.